1965
DOI: 10.1115/1.3650603
|View full text |Cite
|
Sign up to set email alerts
|

The Static and Dynamic Characteristics of the Spiral-Grooved Thrust Bearing

Abstract: A generalized analysis for spiral-grooved thrust bearings is presented. The effects of local radius are considered. For the same grooving geometry and the same inside-to-outside radius ratio, the inflow design is shown to be superior in both stiffness and load capacity. The analysis also treats a relative, transverse, oscillatory motion of the bearing surfaces. Both the magnitude and phase angle (in the temporal sense) of the bearing reaction are dependent on the frequency of the motion. The results for the os… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
34
0

Year Published

1974
1974
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(34 citation statements)
references
References 0 publications
0
34
0
Order By: Relevance
“…The possibility of a self-acting gas-lubricated, thrust bearing to experience 'k a self-excited instability was realized in a theoretical study which was concerned with the operation of the spiral-groove thrust bearing at a large compressibility number [23]. It was found that the quasi-dynamic damping coefficient of a spiral groove thrust bearing, which is optimized for maximum load capacity, can become negative with respect to a translational axial perturbation if the effective compressibility number exceeds a value between 12.0 and 16.0 depending on the radius ratio.…”
Section: Stability Of Thrust Bearingsmentioning
confidence: 99%
See 1 more Smart Citation
“…The possibility of a self-acting gas-lubricated, thrust bearing to experience 'k a self-excited instability was realized in a theoretical study which was concerned with the operation of the spiral-groove thrust bearing at a large compressibility number [23]. It was found that the quasi-dynamic damping coefficient of a spiral groove thrust bearing, which is optimized for maximum load capacity, can become negative with respect to a translational axial perturbation if the effective compressibility number exceeds a value between 12.0 and 16.0 depending on the radius ratio.…”
Section: Stability Of Thrust Bearingsmentioning
confidence: 99%
“…However, variation of sliding speed and the area constriction with radius were neglected. Subsequent studies [23,87,88] revealed that the inward pumping design is invariably the best grooving pattern. Its relative superiority over alternative configurations is associated with annular geometries with a relatively small inner/outer radius ratio (<0.6) and a relatively large compressibility number.…”
mentioning
confidence: 99%
“…Therefore, hydrodynamic thrust air bearings are extremely effective against saving of energy gain recognition in today's machine industry. The study related to hydrodynamic thrust air bearings has been previously performed by a lot of researchers [1][2][3][4][5][6][7]. On the other hand, bearing stiffness is considerably low compared with oil bearing because the viscosity of air is very low.…”
Section: Introductionmentioning
confidence: 99%
“…The theoretical studies on air film thrust bearings have been presented by many investigators, for example, by Ausman (2) , Castelli (3) , Artiles (4) , Shapiro (5) , Maranoski (6) , James (7) , Lipschity (8) , and Bonneau (9) . On the other hand, the experimental studies on the bearings have been carried out by Rood (10) , Maranoski (11) , Nemeth (12) , Hughes (13) and Hashimoto (14) .…”
Section: Introductionmentioning
confidence: 99%